A. Philip Randolph papers - Randolph, A. Philip (Asa Philip), 1889-1979.; A. Philip Randolph Institute
Correspondence, memoranda, speeches and writings, subject files, legal papers, family papers, biographical material, and other papers pertaining to Randolph and his work as a civil rights leader and an African-American union official. Documents his strategy for securing political, social, and economic rights for African-Americans. Subjects include the A. Philip Randolph Institute's "Freedom Budget," the Brotherhood of Sleeping Car Porters, civil rights movement and demonstrations, the Fair Employment Practices Committee, March on Washington Movement, the Messenger, military discrimination, National Association for the Advancement of Colored People, National Educational Committee for a New Party, Negro American Labor Council, Pan-Africanism, the Prayer Pilgrimage for Freedom, May 17, 1957, in Washington, D.C., socialism, the White House Conference To Fulfill These Rights, 1966, and the Youth March for Integrated Schools, Washington, D.C., Oct. 25, 1958.
Correspondents include Hazel Alves, Theodore E. Brown, Charles Wesley Burton, Roberta Church, Thurman L. Dodson, Dwight D. Eisenhower, Lester B. Granger, William Green, Anna Arnold Hedgeman, Anna Rosenberg Hoffman, Hubert H. Humphrey, Lyndon B. Johnson, Maida Springer Kemp, John F, Kennedy, Martin Luther King, Jr., Rayford Whittingham Logan, Emanuel Muravchik, Philip Murray, Chandler Owen, Cleveland H. Reeves, Walter Reuther, Grant Reynolds, Eleanor Roosevelt, Franklin D. Roosevelt, Norman Thomas, Harry S. Truman, Wyatt Tee Walker, Walter Francis White, Roy Wilkins, and Aubrey Willis Williams.
Microfilm edition of selections available, no. 20,562; cataloged in record 91011920.
Library of Congress Prints and Photographs Division.
Civil rights leader and labor union official. Died 1979.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Alves, Hazel -- Correspondence; Brown, Theodore E. -- Correspondence; Burton, Charles Wesley, -- 1897- -- Correspondence; Church, Roberta -- Correspondence; Dodson, Thurman L. -- Correspondence; Eisenhower, Dwight D. -- 1890-1969 -- Correspondence; Granger, Lester B. -- 1896-1976 -- Correspondence; Green, William, -- 1870-1952 -- Correspondence; Hedgeman, Anna Arnold, -- 1899-1990 -- Correspondence; Hoffman, Anna Rosenberg, -- 1902-1983 -- Correspondence; Humphrey, Hubert H. -- 1911-1978 -- Correspondence; Johnson, Lyndon B. -- 1908-1973 -- Correspondence; Kemp, Maida Springer -- Correspondence; Kennedy, John F. -- 1917-1963 -- Correspondence; King, Martin Luther, -- Jr., -- 1929-1968 -- Correspondence; Logan, Rayford Whittingham, -- 1897-1982 -- Correspondence; Muravchik, Emanuel -- Correspondence; Murray, Philip, -- 1886-1952 -- Correspondence; Owen, Chandler, -- 1889-1967 -- Correspondence; Reeves, Cleveland H. -- Correspondence; Reuther, Walter, -- 1907-1970 -- Correspondence; Reynolds, Grant -- Correspondence; Roosevelt, Eleanor, -- 1884-1962 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Thomas, Norman, -- 1884-1968 -- Correspondence; Truman, Harry S., -- 1884-1972 -- Correspondence; Walker, Wyatt Tee -- Correspondence; White, Walter Francis, -- 1893-1955 -- Correspondence; Wilkins, Roy, -- 1901-1981 -- Correspondence; Williams, Aubrey Willis, -- 1890-1965 -- Correspondence; Randolph family; United States. -- Fair Employment Practices Committee; Brotherhood of Sleeping Car Porters; March on Washington Movement; National Association for the Advancement of Colored People; National Educational Committee for a New Party; Negro American Labor Council; Messenger; African American labor union members; African Americans -- Civil rights; African Americans -- Economic conditions; African Americans -- Politics and government; African Americans -- Social conditions; Civil rights -- United States; Civil rights demonstrations -- United States; Discrimination in employment -- United States; Economic assistance, Domestic -- United States; Pan-Africanism.; Race discrimination -- United States; Socialism; United States -- Armed Forces -- African Americans; United States -- Race relations; Civil rights leaders; Labor leaders